Disasters with oil spills in the oceans: Impacts on food safety and analytical control methods. (July 2022) - Zapelini de Melo, Ana Paula; Hoff, Rodrigo Barcellos; Molognoni, Luciano; de Oliveira, Thais; Daguer, Heitor; Manique Barreto, Pedro Luiz
Graphical abstract: Highlights: Oil spills disasters severely impacted the seafood sanitary credibility. Polycyclic aromatic hydrocarbons are markers of petrogenic contamination in seafood. Food intake with polycyclic aromatic hydrocarbons is related to cancer. Reliable analytical methods must be available in an oil spill scenario. An insightful and guiding tool of the risk assessment steps is provided. Abstract: More than 5.8 million tonnes of oil have been spilled into the oceans. Some oil disasters marked history, causing multiple social and economic consequences in addition to catastrophic environmental impacts. Recently, Brazil and Mauritius faced oil disasters that have severely impacted seafood sanitary credibility. One of the components of the oil composition are the polycyclic aromatic hydrocarbons (PAH), which are the main contamination markers of petrogenic origin. There is enough evidence to correlate the intake of food contaminated with PAH with increased risks of developing cancer. The set PAH4, composed of benzo[ a ]anthracene, benzo[ a ]pyrene, benzo[ b ]fluoranthene, and chrysene, and the set PAH8, composed of benzo[ a ]anthracene, benzo[ a ]pyrene, benzo[ b ]fluoranthene, benzo[ k ]fluoranthene, benzo[ ghi ]perylene, chrysene, dibenzo[ a, h ]anthracene, and indeno[1, 2, 3- cd ]pyrene are recognized as markers of food chemical contamination. After oil disasters in the oceans, the risk to the health of seafood consumers tends to be of special concern, Countries like the European Union set maximum levels for benzo[ a ]pyrene (5 µg kg −1 ) and PAH4 (30 µg kg −1 ) in bivalve mollusks. Levels of concern established by countries that have faced oil disasters are given special attention in this review. Laboratory analysis of PAH in food samples is very challenging because it deals with quite different kinds of matrices. Furthermore, analytical results are usually related to the closure or reopening of cultivated areas and fishing points. Therefore, the progress of the analytical methods for PAH in seafood is covered in detail. Chemical laboratory measurements provide essential data to assess the potential risks to human health due to consumption of seafood contaminated with PAH. The main human health risk assessment approaches in a seafood contamination scenario with PAH are reviewed and discussed, providing an insightful and guiding tool to each step of the risk assessment framework.